Analisis Wasei Eigo dalam Pamflet Digital Perhotelan Jepang - Dwi PUSPITOSARI; ALISHA RAFA NURMAULIA (Mezurashii: Journal of Japanese Studies, 2026)
Wasei eigo usage in Japanese advertising media continues to grow, one of which is in digital hotel pamphlets. These loanwords often resemble English in sound, yet their meanings have shifted or may even be unrecognizable to native English speakers. This study aims to identify the types of wasei eigo found in Japanese digital hotel pamphlets based on the classification by Hirai (2003), and to analyze the semantic changes using the theory of meaning change by Chaer (2013). A qualitative descriptive approach was employed, utilizing observation and note-taking techniques. The data source consisted of 18 Japanese digital hotel pamphlets obtained from official websites between December 2024 and March 2025. The analysis revealed that out of 37 wasei eigo entries identified, the most common types were compound (ketsugougata) and clipped (shouryakugata), each accounting for 11 entries. In terms of semantic change, 9 words exhibited narrowing, 8 showed broadening, 6 underwent total shifts, 2 experienced euphemism, and 12 did not undergo any semantic change. These findings indicate that in the context of hotel promotion, wasei eigo serves not only as a communication tool but also as a marketing strategy, creating a modern impression and enhancing comprehensibility for the Japanese audience.